ANALISIS FAKTOR KEAMANAN PADA JEMBATAN KERETA API BH NOMOR 998 KM 419+893 ANTARA STASIUN MERAPI DAN STASIUN SUKACINTA DI DIVRE 3 PALEMBANG - Dicky Arisikam; Heru Kuswanto; Muhammad Arifudin; Alya Ramadianisa (Jurnal Ilmiah Teknologi Infomasi Terapan, 2022)
On the railway bridge, there are calculated loads. Loads are grouped into three, namely girder loads, additional dead loads, and live loads. Currently, the train load is planned based on the Live Load (RM) 1921 scheme. On the bridge, BH Number 998 which connects Merapi Station with Sukacinta Station is passed by 2 CC 204 locomotives and 60 PPCW wagons. Load analysis was carried out by determining the axle load and axle distance adjusted to spans of 30 m, 40 m, and 60 m. Then, we can do a comparison with the realization of the existing load. The calculation results show that span 60 has a safety factor value of more than 1.5. So, it can be concluded that the live load that crosses the BH Number 998 bridge at span 60 has met SNI.